Description of Public Perception of the Function of Political Parties - Silahudin Silahudin; Sri Lestari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The existence of political parties is a logical consequence in the life of a state that adheres to a democratic system. The growth and development of the existence of the political party is very dependent on the voters (public choice). The focus of the survey or research aims to describe and at the same time analyze the public's perception as a public choice of the function of political parties and the reasons they convey. So that this research method was carried out by means of a survey with questions submitted through a google form that was made strictly so that respondents could not fill it out repeatedly with the survey area being Bandung Regency, West Bandung Regency, and Bandung City. Furthermore, the questionnaire is delivered or distributed through social media (WhatsApp) a network of friends in a row. The overview of the survey results in general, the public choice gives an important meaning to the functions of political parties that must be carried out by political party actors, even though they have not worked as expected.